Integrated microprofilometry and multispectral imaging for full-field analysis of ancient manuscripts. - Mazzocato, S.; Cimino, D.; Daffara, C. (Journal of Cultural Heritage, 2024)
• Optical scanner microprofilometry for surface analysis of book heritage. • Integration of microprofilometry and multispectral imaging for materials-surface analysis of manuscripts. • Spatial registration of microsurface and multispectral images combining height-intensity datasets. • Multispectral image-guided microsurface analysis for segmentation and investigation of degraded book heritage. A novel workflow is proposed to combine the use of two powerful techniques in the study of ancient manuscripts: multispectral imaging and optical microprofilometry. Multispectral imaging is routinely used and allows to examine each individual folium as a superposition of layers that give different responses in the UV-Vis-NIR bands. It enables the analysis of the conservation state of an object, the mapping of previous restorations or the detection of writings no longer visible. The downside of this technique is the lack of quantitative data on surface morphology. On the other hand, surface microprofilometry on book heritage is unexplored. The optical scanning microprofilometer used in this work employs single-point, interferometric depth-sensors that enable to measure the surface topography of the manuscript (deformation and roughness) in full-field (areas of tens of centimeters) at micrometer scale. The crucial task of spatial referencing the surface topography at micrometer scale to the visible features (e.g., written text) is performed with a novel procedure that solves the problem of the lack of reference points in the microprofilometer height data. We exploit the raw intensity signal collected by the laser depth sensor to fuse the interferometric measurements with the multispectral image stack. The full-field integration of quantitative microsurface measurements and in-band imaging responses enables a more comprehensive exploration of ancient manuscripts, by integrating materials-surface analysis, advancing the diagnostic protocol.